2022
DOI: 10.1002/suco.202200718
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prediction of the effect of Nanosilica on the compressive strength of concrete with different mix proportions and specimen sizes using various numerical approaches

Abstract: Introducing nanotechnology in concrete is one of the most significant successes in enhancing the mechanical properties of concrete. It affects the quality of the microstructure of the concrete due to its extremely small nanoparticles leading to a faster reaction due to its large surface area. The nanoparticles fill the concrete's pores, resulting in considerably improved strengths in the early ages of the concrete. This research used six models; linear regression (LR), multilinear regression (MLR), nonlinear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 57 publications
(167 reference statements)
0
9
0
Order By: Relevance
“…One is that the high pozzolanic activity of NS can promote hydration, the reaction between SiO 2 and cement hydration product Ca(OH) 2 produces C-S-H gels, subsequently the generated C-S-H gels can fill the pores in SCC. 6,29,31,64,84,86,87 Furthermore, nano-particles have great surface energy, and nano-particles are closely combined with cement hydration products, which can promote C-S-H gels to adhere to the NS particles, making the structure of C-S-H gels more stable. 88,89 For instance, after 28-days of curing, compared with the control group (see Figure 10a), the C-S-H gels of SCC containing 3% NS are more evenly distributed (see Figure 10b), and no obvious pores are observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is that the high pozzolanic activity of NS can promote hydration, the reaction between SiO 2 and cement hydration product Ca(OH) 2 produces C-S-H gels, subsequently the generated C-S-H gels can fill the pores in SCC. 6,29,31,64,84,86,87 Furthermore, nano-particles have great surface energy, and nano-particles are closely combined with cement hydration products, which can promote C-S-H gels to adhere to the NS particles, making the structure of C-S-H gels more stable. 88,89 For instance, after 28-days of curing, compared with the control group (see Figure 10a), the C-S-H gels of SCC containing 3% NS are more evenly distributed (see Figure 10b), and no obvious pores are observed.…”
Section: Discussionmentioning
confidence: 99%
“…As a SCM for SCC, NS usually plays two roles. One is that the high pozzolanic activity of NS can promote hydration, the reaction between SiO2 and cement hydration product Ca(OH) 2 produces C‐S‐H gels, subsequently the generated C‐S‐H gels can fill the pores in SCC 6,29,31,64,84,86,87 . Furthermore, nano‐particles have great surface energy, and nano‐particles are closely combined with cement hydration products, which can promote C‐S‐H gels to adhere to the NS particles, making the structure of C‐S‐H gels more stable 88,89 .…”
Section: Mechanical Properties Of Scc Containing Nsmentioning
confidence: 99%
“…All input parameters were determined to have a wide range. 31 Because there was no appreciable overlap in the seven-dimensional input space, statistical analysis showed that the choice of these input variables was reasonable. [32][33][34][35][36] In addition, the histograms in Figure 1 graphically show the distributions of the variables.…”
Section: Datasetmentioning
confidence: 99%
“…Nanotechnology is widely used in construction projects by improving the properties of building materials by modifying or enhancing microstructures at the nanoscale. Furthermore, a small amount of pozzolanic NMs can be used to improve the performance of UHPC by enhancing the mechanical and durability property due to pozzolanic reaction, nucleation effect, and filler 51–53 . As such, a growing number of studies have been conducted on the use of nanoparticles, such as nano‐CaCO 3 , nano‐SiO 2 , nano‐TiO 2 , and nano‐Al 2 O 3 , to enhance the properties of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a small amount of pozzolanic NMs can be used to improve the performance of UHPC by enhancing the mechanical and durability property due to pozzolanic reaction, nucleation effect, and filler. [51][52][53] As such, a growing number of studies have been conducted on the use of nanoparticles, such as nano-CaCO 3 , nano-SiO 2 , nano-TiO 2 , and nano-Al 2 O 3 , to enhance the properties of concrete. The use of nano-TiO 2 in concrete works as a photocatalyst and acts as a decomposer for organic pollutants and oxides such as and some oxides (such as NO 2 , NO, and SO 2 ).…”
mentioning
confidence: 99%